Not so deep in the rainforest: two new species of Anastrepha (Diptera, Tephritidae) and a pictorial key to species from Amazonas state, Brazil - Keiko Uramoto; Alexandre S. Araújo; Francisco C. Costa-Silva; Neliton M. Silva; Marcoandre Savaris; Roberto A. Zucchi (ZooKeys)
Two new species, Anastrepha dorsidentata Uramoto, Zucchi, Araújo & Savaris and A. norrbomi Uramoto, Zucchi, Araújo & Savaris, from a fragment of the Amazon Rainforest in the city of Manaus, state of Amazonas, Brazil, are described and illustrated. Both species were collected in McPhail-type traps hanging from trees on the campus of Federal University of Amazon. A pictorial key to 47 species of Anastrepha recorded in Amazonas state is provided.